Sul divieto di dimora del soldato congedato con disonore - Greco, Giovanbattista (Cultura giuridica e diritto vivente, 2020)
[The residence ban applied to soldiers dishonorably discharged] The article compares the residence ban applied in Roman law to soldiers who were dishonorably discharged (ignominia missi) with the ordinary consequences of relegatio. The endorsed hypothesis is that the two example of bans could have been justified by different rationes, supporting the idea that military criminal penalties had not just punitive nature.